Pannexin-2-deficiency sensitizes pancreatic β-cells to cytokine-induced apoptosis in vitro and impairs glucose tolerance in vivo. (15th June 2017) - Berchtold, Lukas A.; Miani, Michela; Diep, Thi A.; Madsen, Andreas N.; Cigliola, Valentina; Colli, Maikel; Krivokapic, Jelena M.; Pociot, Flemming; Eizirik, Decio L.; Meda, Paolo; Holst, Birgitte; Billestrup, Nils; et al.
Abstract: Pannexins (Panx's) are membrane proteins involved in a variety of biological processes, including cell death signaling and immune functions. The role and functions of Panx's in pancreatic β-cells remain to be clarified. Here, we show Panx1 and Panx2 expression in isolated islets, primary β-cells, and β-cell lines. The expression of Panx2, but not Panx1, was downregulated by interleukin-1β (IL-1β) plus interferon-γ (IFNγ), two pro-inflammatory cytokines suggested to contribute to β-cell demise in type 1 diabetes (T1D). siRNA-mediated knockdown (KD) of Panx2 aggravated cytokine-induced apoptosis in rat INS-1E cells and primary rat β-cells, suggesting anti-apoptotic properties of Panx2. An anti-apoptotic function of Panx2 was confirmed in isolated islets from Panx2 -/- mice and in human EndoC-βH1 cells. Panx2 KD was associated with increased cytokine-induced activation of STAT3 and higher expression of inducible nitric oxide synthase (iNOS). Glucose-stimulated insulin release was impaired in Panx2 -/- islets, and Panx2 -/- mice subjected to multiple low-dose Streptozotocin (MLDS) treatment, a model of T1D, developed more severe diabetes compared to wild type mice. These data suggest that Panx2 is an important regulator of the insulin secretory capacity and apoptosis in pancreatic β-cells. Highlights: Pannexin 2 is expressed in pancreatic islets and β-cells. Pannexin 2-deficiency is associated with aggravated islet apoptosis. Pro-inflammatory cytokines suppress pannexin 2 expression. Pannexin 2-deficiency increases the severity of chemically-induced diabetes in mice.